Beta Cell Function, Insulin Resistance and Low Grade Systemic Inflammation in Myanmar Adults with Different Categories of Glucose Tolerance - Than, Mo-Mo-; Thazin, May; Swe Latt, Tint (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Objective. The aim of the study was to evaluate the beta cell function, insulin sensitivity and low grade systemic inflammation in different categories of glucose tolerance in Myanmar. Methodology. A cross-sectional study was conducted on 202 Myanmar subjects of both sexes, aged between 45-65 years old. Fasting blood glucose, insulin, C-peptide and hs-CRP levels were measured. A 75g oral glucose tolerance test was performed. Insulin resistance and beta cell function were assessed by homeostasis-model-assessment (HOMA). Results. The subjects were categorized as normal glucose tolerance (NGT), impaired fasting glucose (IFG), impaired glucose tolerance (IGT) and diabetes mellitus (DM) according to WHO-2006 criteria. Fasting serum insulin, C-peptide and hs-CRP levels and insulin resistance index (HOMA-IR) progressively increased from NGT through prediabetes (IFG, IGT) to DM (p<0.01). Beta-cell function did not change significantly in any other group as compared to normal group. Conclusion. After multivariate analysis, increases in fasting C-peptide, hs-CRP and HOMA-IR index were significantly associated with diabetes. It was also found that insulin resistance was a predominant feature in deterioration of the glucose tolerance in Myanmar subjects.